A shy hope in the heart? Religious journalism in Australia and the Kuyperian legacy - Pass, Bruce R (Stellenbosch Theological Journal, 2017)
This article explores points of contact between Abraham Kuyper’s legacy in the field of religious journalism and the Centre for Public Christianity, an independent media company at the forefront of Australian religious journalism. While the cultural, political, and religious setting of twenty–first century Australia could not be further removed from that of late nineteenth century Netherlands, these two approaches to religious journalism hold much potential for mutual resourcement. The points of contact identified indicate the possibility that Kuyperian principle holds considerable explanatory power for the praxis of the Centre for Public Christianity, just as the praxis of the Centre for Public Christianity exposes underdeveloped elements of Kuyperian principle.